Identification and characterization of phenolics and terpenoids from ethanolic extracts of Phyllanthus species by HPLC-ESI-QTOF-MS/MS - Sunil Kumar; Awantika Singh; Brijesh Kumar (Elsevier, 2017)
Phyllanthus species plants are a rich source of phenolics and widely used due to their medicinal properties. A liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed using high-pressure liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (HPLC-ESI-QTOF-MS/MS) for the identification and characterization of quercetin, kaempferol, ellagic acid and their derivatives in ethanolic extracts of Phyllanthus species. The chromatographic separation was carried out on Thermo Betasil C8 column (250 mm×4.5 mm, 5 µm) using 0.1% formic acid in water and 0.1% formic acid in methanol as the mobile phase. The identification of diagnostic fragment ions and optimization of collision energies were carried out using 21 reference standards. Totally 51 compounds were identified which include 21 compounds identified and characterized unambiguously by comparison with their authentic standards and the remaining 30 were tentatively identified and characterized in ethanolic extracts of P. emblica, P. fraternus, P. amarus and P. niruri.